Implementasi Pembelajaran IPA Berbasis Ekosistem Mangrove sebagai Laboratorium Alam di Ekowisata Bale Mangrove - Hidayat, Sugih Akbar; Oktaviani, Nur Padia; Yuliana, Baiq Fadilla; Ardani, Sarwan; Hatami, Muhamad; Ramdani, Novia; Syukur, Abdul; Handayani, Baiq Sri; Sukma, Izza Melati (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Mangrove ecosystem-based education is very relevant in supporting contextual learning, especially for students living in coastal areas. This program aims to improve students' understanding of mangrove ecosystems through direct exploration at Bale Mangrove Ecotourism, Poton Bako Village, as a natural laboratory. This research uses the Service Learning method with a focus on developing mangrove ecosystem-based teaching materials. The development process was carried out through interviews, observations, and field tests with students of SDN 4 Jerowaru. The results of the community service program conducted by the Bale Mangrove Thematic KKN team from the University of Mataram show that mangrove ecosystem-based teaching materials can increase students' understanding and awareness of the importance of mangroves. Learning conducted in a real and contextual environment allows students to better understand and apply scientific concepts in everyday life. In addition, this program succeeded in increasing students' knowledge about mangrove ecosystems.